Governance and institutional arrangement in floodplain wetlands fisheries of India: comparative study of Assam and Bihar - Chandra, Ganesh; Das, B K (Journal of the Inland Fisheries Society of India, 2020)
Wetlands are amongst the most productive life support systems in the world with immense socio-economic importance and provide food, fodder, fuel and water for domestic, irrigation and industrial uses. India is bestowed with a wealth of wetlands due to wide variation of climatic and topographical features. Two eastern states, Assam & Bihar are endowed with hugeaquatic wealth in the form of wetlands, tanks, ponds and rivers. The floodplain wetlands (beels in Assam and Mauns, chaur in Bihar) extending over one lakh hectare in Assam and more than 200000 ha in Bihar, constitute the most important fishery resource of these two states. These wetlands are considered as one of the most productive ecosystems owing to their interactions between land and water system. Livelihood of fishers'family from time immemorial has been dependent on fishing in these floodplain wetlands. The floodplain wetlands are as multiple uses and multiple user system. These are common property resource and underdifferent management regimes. Multiple institutions play its role through ownership and control over the fisheries of wetlands. A large number of stakeholders associated directly and indirectly with the Wetlands,these include fishers, lessees, various state government departments, fisheries development corporations, financial institutions, research institutes, NGO's etc. These wetlands are under various management regimes,i.e., private management (individuals and groups), fishermen cooperative management, Community-based fisheries management (decentralized management, Government works as facilitator) and open access. Theleasing period for cooperative as well as individual fishers was seven years in both Assam and Bihar. Sustainable fisheries development demands a balancebetween social, environmental and economic parameters and this requires integrated approach and participation of various stakeholders. An attempt has been made through this communication to describe managementregimes and institutional arrangement in the frame work of stakeholders' mechanism of access to utilize the floodplain wetland resources for outcomes (positive or negative).Keywords Floodplain wetland, Common Property Resources, Governance, institutional arrangement, Lessee, Management Regimes, Open access